2017
DOI: 10.1038/s41598-017-06520-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Cyclophosphamide treatment for immunoglobulin G4-related disease with addition of glucocorticoids

Abstract: Aim to evaluate the efficacy and safety of glucocorticoid monotherapy vs combination therapy of cyclophosphamide (CYC) for IgG4 related disease (IgG4-RD). 102 newly diagnosed IgG4-RD patients were enrolled and assigned to 2 groups: Group I was prednisone monotherapy (0.5–1.0 mg/kg.d, tapered gradually) and Group II was glucocorticoid and CYC (50–100 mg per day). Patients were assessed at different periods. Primary end point was relapse rate; secondary end points included response, remission rate and adverse ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
77
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 18 publications
4
77
0
6
Order By: Relevance
“…During follow‐up, the cumulative relapse rates of the cohort were 10.66%, 22.95% and 27.87% at 12, 24 and 36 months, respectively. Consistent with previous findings , recurrence seemed to occur more commonly in the lacrimal glands, salivary glands, lymph nodes, lungs, pancreas and bile duct. The lower relapse rate of GC + IM therapy during the GC tapering and GC maintenance stages indicated that combination with IM had a better effect than GC monotherapy.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…During follow‐up, the cumulative relapse rates of the cohort were 10.66%, 22.95% and 27.87% at 12, 24 and 36 months, respectively. Consistent with previous findings , recurrence seemed to occur more commonly in the lacrimal glands, salivary glands, lymph nodes, lungs, pancreas and bile duct. The lower relapse rate of GC + IM therapy during the GC tapering and GC maintenance stages indicated that combination with IM had a better effect than GC monotherapy.…”
Section: Discussionsupporting
confidence: 91%
“…Using Cox regression and other statistical analyses between relapsed and nonrelapsed patients, we found that the significant predictive factors for IgG4‐RD relapse were high serum IgG4 concentrations (IgG4 level > 27000 mg L −1 ), involvement of more organs, lymphadenopathy, high IgG4 RI scores, low GC maintenance dosage, history of allergies and eosinophilia at baseline. It was reported that neither bile duct involvement nor involvement of other specific organs was associated with disease relapse. However, inconsistent with data from previous reports, we found that lymph node involvement was related to disease relapse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If a patient's IgG4‐RD RI score was 3 points at the beginning, PR was considered as a 1 point decrease after the therapy. Patients with lack of apparent changes in mass sizes and/or clinical manifestations and IgG4‐RD RI scores declining <2 were considered to be NE …”
Section: Methodsmentioning
confidence: 99%
“…Immunoglobulin G4‐related disease (IgG4‐RD) is a newly defined chronic fibro‐inflammatory disorder characterized by elevated serum IgG4 levels, tumefactive lesions with a dense lymphoplasmacytic infiltration rich in IgG4 positive plasma cells and storiform fibrosis of related organs . Glucocorticoids are the first‐line agents for the treatment of IgG4‐RD; however, in order to maintain long‐term disease stability and avoid disease relapse, usually glucocorticoids maintenance therapy should last for a long period, which may induce various glucocorticoid‐associated adverse reactions. For some IgG4‐RD patients with mild symptoms, such as swelling of the lacrimal glands, submandibular glands, parotid glands and nasal sinus, without internal organ damage, long‐term glucocorticoids therapy for mild symptoms may have a low benefit/risk ratio.…”
Section: Introductionmentioning
confidence: 99%